Effectiveness of a killed whole-cell oral cholera vaccine in Bangladesh: further follow-up of a cluster-randomised trial. Issue 10 (October 2021) - Ali, Mohammad; Qadri, Firdausi; Kim, Deok Ryun; Islam, Md Taufiqul; Im, Justin; Ahmmed, Faisal; Khan, Ashraful Islam; Zaman, K; Marks, Florian; Kim, Jerome H; Clemens, John D
Summary: Background: Killed whole-cell oral cholera vaccines (OCVs) are widely used for prevention of cholera in developing countries. However, few studies have evaluated the protection conferred by internationally recommended OCVs for durations beyond 2 years of follow-up. Methods: In this study, we followed up the participants of a cluster-randomised controlled trial for 2 years after the end of the original trial. Originally, we had randomised 90 geographical clusters in Dhaka slums in Bangladesh in equal numbers (1:1:1) to a two-dose regimen of OCV alone (targeted to people aged 1 year or older), a two-dose regimen of OCV plus a water–sanitation–hygiene (WASH) intervention, or no intervention. There was no masking of group assignment. The WASH intervention conferred little additional protection to OCV and was discontinued at 2 years of follow-up. Surveillance for severe cholera was continued for 4 years. Because of the short duration and effect of the WASH intervention, we combined the two OCV intervention groups. The primary outcomes were OCV overall protection (protection of all members of the intervention clusters) and total protection (protection of individuals who got vaccinated in the intervention clusters) against severe cholera, which we assessed by multivariable survival models appropriate for cluster-randomised trials. This trial is registered on ClinicalTrials.gov, NCT01339845 . Findings: The study was done between April 17, 2011, and Nov 1, 2015. 268 896 participants were present at the time of the first dose, with 188 206 in the intervention group and 80 690 in the control group. OCV coverage of the two groups receiving OCV was 66% (123 659 of 187 214 participants). During 4 years of follow-up, 441 first episodes of severe cholera were detected (243 episodes in the vaccinated groups and as 198 episodes in the unvaccinated group). Overall OCV protection was 36% (95% CI 19 to 49%) and total OCV protection was 46% (95% CI 32 to 58). Cumulative total vaccine protection was notably lower for people vaccinated before the age of 5 years (24%; −30 to 56) than for people vaccinated at age 5 years or older (49%; 35 to 60), although the differences in protection for the two age groups were not significant (p=0·3308). Total vaccine protection dropped notably (p=0·0115) after 3 years in children vaccinated at 1–4 years of age. Interpretation: These findings provide further evidence of long-term effectiveness of killed whole-cell OCV, and therefore further support for the use of killed whole-cell OCVs to control endemic cholera, but indicate that protection is shorter-lived in children vaccinated before the age of 5 years than in people vaccinated at the age of 5 years or older. Funding: Bill & Melinda Gates Foundation. Translation: For the Bengali translation of the abstract see Supplementary Materials section.